2010
DOI: 10.3390/ma3125263
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analyses of Fe-based Metallic Glasses by Electron Diffraction

Abstract: Nanoscale structural information of amorphous structures has become obtainable by using nanobeam electron diffraction in combination with high resolution imaging. In addition, accurate radial distribution function analysis using energy filter has also become available to know averaged amorphous structures. In this paper, we introduce some applications of these techniques, especially to several Fe-based metallic glasses. On the basis of these results, we discuss a relationship between the glass structure and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…39 The oxides in the carbon films have mostly carboxylic functions and act as anchors for the FeNPs, presumably through an ionexchange reaction, to produce material that consists of FeNPs with average size between 1 and 7 nm. 40 Therefore, FeNPs are trapped inside the carbon trace films and will not be agglomerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The oxides in the carbon films have mostly carboxylic functions and act as anchors for the FeNPs, presumably through an ionexchange reaction, to produce material that consists of FeNPs with average size between 1 and 7 nm. 40 Therefore, FeNPs are trapped inside the carbon trace films and will not be agglomerated.…”
Section: Discussionmentioning
confidence: 99%
“…Then the dangling bonds around the defective vacancies can provide active sites for FeNP adsorption . The oxides in the carbon films have mostly carboxylic functions and act as anchors for the FeNPs, presumably through an ion-exchange reaction, to produce material that consists of FeNPs with average size between 1 and 7 nm . Therefore, FeNPs are trapped inside the carbon trace films and will not be agglomerated.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary for a relatively small mxn product, the structural units might move each with respect to the others with center to center distance variations and local volume contraction or expansion. Different atomic clusters may exist that also possess high local packing efficiency and may act as such structural units: The capped trigonal prism, and a coordination number of 9, and icosahedra, with a coordination number of 12, are two such solute-centered clusters that are known to exist in metallic glass structures 25,26 . The change in the composition for a given system leads to a progressive shift from a given interpolation line to another in Fig.…”
Section: V=v O ) Leads Tomentioning
confidence: 99%
“…Comparing metallic glasses from different chemical systems remains difficult though, probably because an average packing efficiency (Eq. 1) doesn't take into account the spatial distribution of the packing density 26 , as well as the incidence of the local packing geometry and coordination 25 . For instance, in spite of a mostly smaller C g for Pt-based glasses than for Cu-based glasses (Fig.…”
Section: Elastic Moduli and Glass Transition Rangementioning
confidence: 99%
“…They concluded that Fe 90 Sc 10 melt-spun ribbons contain a high density of distorted bcc-Fe (bcc-Fe like) clusters on the basis of the similarity of RDFs of the Fe 90 Sc 10 melt-spun ribbons and bcc-Fe crystals. Hirata et al [19] deduced plausible structure models for Fe-based MQMG using ED intensity analysis with the help of reverse Monte Carlo simulation. In fact, they also proposed that bcc-Fe like clusters are the dominant feature of the SRO of Fe-based MQMG, and the ratio of bcc-Fe like clusters increases with increasing the Fe concentration.…”
mentioning
confidence: 99%